Density functional study of spin polarization on a carbon material with a hexagonal structure induced by iron atoms - Muhida, Rifki; Rahman, Md. Mahmudur; Chowdhury, Md. Sazzad Hossien; Setiyanto, Henry; Zainuddin, Hishamuddin; Zakaria, Azmi; Kasai, Hideaki (American Scientific Publishers, 2014)
We investigate the spin polarization of a non magnetic material, e.g., a carbon material made from ten C atoms forming a hexagonal structure with total spin S = 0, induced by a ferromagnetic material, e.g., two Fe atoms with a total spin S = 4. Based on the density functional theory, we calculate the total spin density of the system. Our preliminary results show that the total spin for the ten C atoms changes from S = 0 to S = 4, while the total spin of the two Fe atoms changes from S = 4 to S =0. These results seem to indicate that there is a promising possibility to induce spin polarization on a carbon material by Fe atoms.